Soil erosion analysis using prime meridian GIS package - Buyong, Taher (UTM, 2001)
A number of soil erosion models have been developed to predict and characterize the movement of soil. These models provide an understanding of the dynamics of soil and can be used to evaluate the effectiveness of land management practices. Nevertheless, modellers faced some major problems. They are the inability to efficiently handle, manipulate and manage large volumes of model parameters. However, recent developments in Geographic Information Systems (GIS) provide the opportunities and tools to spatially organize and effectively manage data for the modelling. Thus, this research aims to develop an interactive soil erosion modelling and prediction system within a GIS environment. Prime Meridian GIS' Spatial Database Engine by Essential Planning System Pte. Ltd. (EPS), will be the core of the designed system. This system is designed to use the universal soil loss equation and the overlay modelling technique to generate the soil erosion risk map. The goal of developing the system is to provide a spatial decision support tool in environmental impact assessment as required by the Department of Environment, Ministry of Science Technology and Environment.